Technology-Based Re-Engineering Engineering Education Proceedings of Frontiers in Education FIE'96 26th Annual Conference
DOI: 10.1109/fie.1996.567770
|View full text |Cite
|
Sign up to set email alerts
|

Using visualization tools to improve undergraduates understanding of crystal structure

Abstract: In order to understand many of the important ideas in materials science, students need to have some understanding of crystal structure and symmetry. But many undergraduate students find crystal symmetry a difJicult and highly abstract subject. One of the reasons for this is the use of difJicult 2 -0 representations of complicated 3-0 structures. Although many teachers use physical models to help give their students a sense of the structure, physical models are limited in the informution they can provide. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It has been consistently reported that many students have difficulties understanding the principles of atom packing, unit cells, and crystal lattices. Thus, conventional teaching strategies and resources have been criticized for being ineffective at communicating these concepts . One reason for those difficulties may be that students are asked to connect models of atoms, traditionally communicated through two-dimensional projections (Figure ) and simple physical models, with macroscopic behavior …”
Section: Introductionmentioning
confidence: 99%
“…It has been consistently reported that many students have difficulties understanding the principles of atom packing, unit cells, and crystal lattices. Thus, conventional teaching strategies and resources have been criticized for being ineffective at communicating these concepts . One reason for those difficulties may be that students are asked to connect models of atoms, traditionally communicated through two-dimensional projections (Figure ) and simple physical models, with macroscopic behavior …”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Foley [6] developed a computer program, CrystalVis, to teach students about crystal structures with a focus on crystallographic notation and crystal symmetry. Since then, other software programs have been developed to visualize crystal structures, such as CrystalMaker [7] and Luealamai and Panijpan's computer game on unit cells [8].…”
Section: Teaching Crystal Structuresmentioning
confidence: 99%